Upaya Diplomasi Perbatasan Indonesia Dalam Menyelesaikan Persoalan Perbatasan Di Tanjung Datu, Kalimantan Barat - Iva Rachmawati; Machya Astuti Dewi (Eksos LPPM, 2020)
This article intends to review the efforts of border diplomacy undertaken by Indonesia in maintaining the Indonesia-Malaysia border in Tanjung Datu, Paloh Subdistrict, Sambas Regency, West Kalimantan. Tanjung Datu is one of the Indonesia-Malaysia borders which still leaves obstacles because at the Tanjung Datu border in Camar Bula, Malaysia no longer recognizes it as part of the OBP or the Oustanding Boundary Problems. While at the Tanjung Datu border in Gosong Niger, it still leaves concern because there are some efforts made by Malaysia to change the country's borders. Both the border in Gosong Niger and in Gamar Bulan, both of which have raised issues that affect good relations between the two countries. Through a qualitative approach based on direct observation study, documentation and in-depth interviews with several parties related to Indonesian border diplomacy, this article suggests that border diplomacy conducted by Indonesia does not involve many important actors at the subnational level related to the implementation of border diplomacy. Some miscommunications and misinformation took place so that Indonesia's border diplomacy was not carried out optimally.